(untitled) - Clinton, Bill (New York, 2004)
President Bill Clinton's My Life is the strikingly candid portrait of a global leader who decided early in life to devote his intellectual and political gifts, and his extraordinary capacity for hanrd work, to serving the public.
Keywords: Presidents,Large type books; Biography; United States